Changes in vegetation structure of «Yelanetsky steppe» during the first decade since it has become protected (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Author reinvestigated plant cover in natural reserve « Yelanetsky steppe» (1675.5 ha, Mykolayiv region) after 10 years of fixing its original state (1997-2007). The main attention was focused on the absolutely protected steppe with no impact of human-induced fire (93 ha). Shrub-steppe communities with Сaragana frutex are spread here with increasing number of Crataegus monogyna, Rhamnus cathartica, Rosa corymbifera etc. Distribution of Stipa capillata, S. lessingiana, S. ucrainica, Festuca valesiaca has been nearly three times decreased on absolutely protected steppe. Being still dominated, these communities was added by relatively mesophytic communities of Poa angustifolia. In general, reserve steppe vegetation demutated only sporadically because of fires, especially in droughty 2007, wich caused their significant degradation. Postexarational demutation of fallow land was quite intensive and reached the stage of Poeta angustifoliae with the complex of forb communities and naturalized trees and shrubs from the surrounding hedgerows.
Keywords: steppe reserve, repeating investigations, demutation of vegetation, postpyrogenic degradation.